Chamomile essential oils exert anti-inflammatory effects involving human and murine macrophages: Evidence to support a therapeutic action. (15th July 2023) - De Cicco, Paola; Ercolano, Giuseppe; Sirignano, Carmina; Rubino, Valentina; Rigano, Daniela; Ianaro, Angela; Formisano, Carmen
Abstract: Ethnopharmacological relevance: Chamomile ( M. chamomilla L.) is an herbaceous plant from family Astereaceae, that has a long history of use in traditional medicine. It has been used as herbal remedies for thousands of years to treat several diseases, including infections, neuropsychiatric, respiratory, gastrointestinal, and liver disorders. Chronic inflammation is involved in the pathogenesis of most infectious and non-infectious diseases and macrophages are considered the major cellular players that drive disease initiation and maintenance. Aim of the study: The aim of this study was to evaluate the variation in the chemical profile of the essential oil of M. chamomilla plants collected in three experimental field sites in the Molise region. Additionally, we evaluated the pharmacological mechanism behind the anti-inflammatory effect of M. chamomilla essential oils. Material and methods: Three essential oils (called GC1, GC2 and GC3) were extracted from aerial parts of M. chamomilla by hydrodistillation and chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS). The essential oils were tested for their ability to modulate pro-inflammatory murine macrophages and human peripheral blood mononuclear cells (PBMCs) functions. Results: The chemical analysis of the samples revealed the presence of a high content of the oxygenated sesquiterpenes that represented more than the half of the entire oils. GC1, GC2 and GC3 essential oils significantly attenuated LPS/IFN-γ-induced inflammation by reducing M1 polarization. In details, they showed significant anti-inflammatory property by inhibiting NO, TNF-α and IL-6 production. These effects were correlated to a suppression of LPS-mediated p65 activation, the critical transactivation subunit for NF-κB transcription factor. Oxidative stress may trigger macrophages activation and elicit strong immune responses. Our study demonstrated that GC1, GC2 and GC3 were highly effective at increasing GCL and HMOX-1 anti-oxidant enzymes expression leading to the rapid scavenging of ROS. The antioxidant activity of these oils was explained throughout the activation of NRF2 signaling pathway. Next, we demonstrated that essential oils were able to reduce CD4 + T cell activation which are also involved in inflammatory processes. Conclusions: Our data describe for the first time that chamomile essential oils exerted their anti-inflammatory and antioxidant activity by modulating macrophages and CD4 + T cells-mediate immune response. Graphical abstract: Image 1 Highlights: Three essential oils were extracted from aerial parts of M. chamomilla by hydrodistillation. The pharmacological mechanism behind the anti-inflammatory effect of M. chamomilla essential oils has been analyzed. The antioxidant activity of EOs was explained throughout the activation of NRF2 signaling pathway. EOs were able to reduce CD4 + T cell activation which are also involved in inflammatory processes.